Physical Activity and Plasticity of the Skeletal Musculature - Bicudo, José Eduardo P. W. (Revista da Biologia, 2018)
The vertebrate skeletal musculature of contemporary humans, responsible for most of their locomotor activity, expresses a common basic structure and mechanism, which resulted from a long evolutionary process. However, the type of physical activity performed may alter these structural and functional patterns. Athletes engaged in different types of training such as velocity, force and endurance express different phenotypes. Athletes engaged in velocity and force sport modalities, like the 100 meters sprint and the shot put, respectively, show predominantly fast twitching muscle fibers, which function in the absence of oxygen (glycolytic pathway), whereas athletes engaging in long term (endurance) modalities, like the marathon, show predominantly slow twitching muscle fibers whose function depends on oxygen (oxidative pathway). These different muscle fiber expressions are known as phenotypic plasticity, which occurs both within the same species as well as among different species.